Implications of bipolar voltage mapping and magnetic resonance imaging resolution in biventricular scar characterization after myocardial infarction. Issue 1 (18th September 2018) - López-Yunta, Mariña; León, Daniel G; Alfonso-Almazán, José Manuel; Marina-Breysse, Manuel; Quintanilla, Jorge G; Sánchez-González, Javier; Galán-Arriola, Carlos; Cañadas-Godoy, Victoria; Enríquez-Vázquez, Daniel; Torres, Carlos; Ibáñez, Borja; Pérez-Villacastín, Julián; et al.
Abstract: Aims: We aimed to study the differences in biventricular scar characterization using bipolar voltage mapping compared with state-of-the-art in vivo delayed gadolinium-enhanced cardiac magnetic resonance (LGE-CMR) imaging and ex vivo T1 mapping. Methods and results: Ten pigs with established myocardial infarction (MI) underwent in vivo scar characterization using LGE-CMR imaging and high-density voltage mapping of both ventricles using a 3.5-mm tip catheter. Ex vivo post-contrast T1 mapping provided a high-resolution reference. Voltage maps were registered onto the left and right ventricular (LV and RV) endocardium, and epicardium of CMR-based geometries to compare voltage-derived scars with surface-projected 3D scars. Voltage-derived scar tissue of the LV endocardium and the epicardium resembled surface projections of 3D in vivo and ex vivo CMR-derived scars using 1-mm of surface projection distance. The thinner wall of the RV was especially sensitive to lower resolution in vivo LGE-CMR images, in which differences between normalized low bipolar voltage areas and CMR-derived scar areas did not decrease below a median of 8.84% [interquartile range (IQR) (3.58, 12.70%)]. Overall, voltage-derived scars and surface scar projections from in vivo LGE-CMR sequences showed larger normalized scar areas than high-resolution ex vivo images [12.87% (4.59, 27.15%), 18.51% (11.25, 24.61%), and 9.30% (3.84, 19.59%), respectively], despite having used optimized surface projection distances. Importantly, 43.02% (36.54, 48.72%) of voltage-derived scar areas from the LV endocardium were classified as non-enhanced healthy myocardium using ex vivo CMR imaging. Conclusion: In vivo LGE-CMR sequences and high-density voltage mapping using a conventional linear catheter fail to provide accurate characterization of post-MI scar, limiting the specificity of voltage-based strategies and imaging-guided procedures.